CATALITYC CONVERTER JENIS KATALIS PIPA TEMBAGA BERLUBANG UNTUK MENGURANGI EMISI KENDARAAN BERMOTOR - Mokhtar, Ali (Jurnal Gamma, 2012)
Catalityc Converter Jenis Katalis Pipa Tembaga Berlubang Untuk Mengurangi Emisi Kendaraan Bermotor Ali MokhtarStaf Pengajar Jurusan Teknik Mesin, Fakultas TeknikUniversitas Muhammadiyah MalangEmail : alimokhtar011@gmail.com, balimokhtar06@yahoo.co.idABSTRACTDecreased levels of exhaust emissions are influenced by the catalyst material and shape of  the catalyst, the catalyst model of perforated pipes showed oxidation and reduction process goes  well, it is shown that the levels of CO2   decreased by 49.7338%, while CO emissions fell by 36.904% and the emissions HC decreased by 28.354%. In general installation catalityc hollow pipe catalytic converter type can reduce exhaust emissions compared with using ctalityc converter.Key Word : copper pipe perforated catalyst